Field and dip data - central Northern Calcareous Alps (Eastern Alps, Austria) - Fernandez, Oscar; Eggerth, Lino (PANGAEA, 2025)
Field dip data has been collected in the central Northern Calcareous Alps (Eastern Alps, Austria and SW Germany) during during field campaigns spanning 2020-2023. The study area spans from 12°30' to 14°30'E and from 47°20 to 48°N (this is an area covering from around Lofer, Austria, in the west to around Liezen, Austria, in the east, and between the SEMP (Salzach-Ennstal-Mariazell-Puchberg) fault to the south and the frontal thrust of the NCA (Northern Calcareous Alps) to the north. Lithostratigraphy used in this dataset is that of Fernandez et al. (2024). Data are collected in dip azimuth and dip and are predominantly bedding data. For non-bedding measurements, the type of structure measured (e.g., fault, fracture) is indicated. Data are in WGS84 UTM33 coordinates.
Keywords: Dip data; Northern Calcareous Alps